Anatomy of neuropsychiatry : the new anatomy of the basal forebrain and its implications for neuropsychiatric illness - Heimer, Lennart (Elsevier, 2008)
An anatomical systems analysis of brain structures and pathways relating to emotion, motivation, memory and adaptive behaviors.